"Audience Rhetoric: Concepts and Applications – Epistemological and Methodological Issues... and the Limits of Theorization" - Abu Shihab, Rami (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract The purpose of this research is to provide a critiquing reading for cognitive foundations and the practical tools of "Audience Rhetoric book, which comes as a theoretical and practical attempt to support this research path that is launched by Emad Abdullatif. It is determined by trying to develop an applied knowledge of what has become known as Audience Rhetoric. The hypothesis of this research is determined by the availability of monetary and cognitive tools for this endeavour based on the renewal of Arabic rhetorics through an analytical methodology. This adopts the test of monetary discourse according to the references adopted by the research, as well as monitoring the theoretical and applied effectiveness through analysing the approach to contribute to the development of the critical perception of meditative studies that came from the presence of some researchers involved in this book.